Early Life Management of Osteogenesis Imperfecta - Arundel, Paul; Borg, Stephanie A. (Current osteoporosis reports, 2023)
Purpose of Review This review aims to provide a review of the multidisciplinary management of infants with osteogenesis imperfecta (OI) during the first year of life, focusing on those with severe disease. The authors draw on published literature and direct experience of working in a large paediatric centre specialising in the management of rare bone disease. Recent Findings Whilst understanding of the pathophysiology of OI has grown over the past decade, the evidence base for management of infants remains limited. There has been a greater recognition of certain subjects of concern including pain management, cervical spine deformity, and neurocognitive development. Both international consensus guidelines on rehabilitation and disease-specific growth charts have been welcomed by clinical teams. Summary The early involvement of multidisciplinary specialist care is critical in ensuring optimal care for the infant with severe OI. A long-term perspective which focuses on the axial, craniofacial, and peripheral skeleton as well as on development more generally provides a framework which can guide the management of infants with severe OI.